Pol`and`Rock Festival jako wydarzenie medialne = Pol`and`Rock Festival as a Media Event - Frąckowiak, Kacper (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to discuss the Pol`and`Rock Festival (formerly Przystanek Woodstock) as a media event. Therefore, all types of media events will be presented: contests, conquests and coronations. The research material, consisting mainly of video materials provided by the organizer (The Great Orchestra of Christmas Charity Foundation), was limited to one edition of the festiwal in 2019. The analysis proved that the Pol`and`Rock Festival is a media event and allowed to assign it to the type of coronation.
Keywords: Pol`and`Rock Festival; wydarzenie medialne; konkurs; konkwista; koronacja; media events; contest; conquest; coronation